Polycystic Ovary Syndrome - increased risk of depression development. Links and risk factors - Szymańska, Julia; Kapłon, Kamil; Pawłocik, Weronika; Wojtala, Laura; Pawlak, Weronika; Kojder, Dominika; Kamińska, Izabela; Grabowska, Ewa; Musiał, Lena; Możdżyńska, Agnieszka (Journal of Education, Health and Sport, 2023)
PCOS is a common endocrine disorder affecting up to 6-10% of women in reproductive age. Patients suffer from many manifestations of this disease including symptoms of hyperandrogenism (hirsutism, acne, androgenetic alopecia), ovulation disorders, infertility, overweight and obesity, glucose-insulin homeostasis disorders (insulin resistance, type 2 diabetes). Many studies emphasize the relationship between the presence of PCOS in patients and the appearance of depression. The median incidence of depression in women with this syndrome was 36.6%, while in the group of women without PCOS it was 14.2%. The exact mechanism of this relationship is still unknown, but many factors may play an important role in it, e.g. increased BMI, infertility, high cortisol levels, body image, vitamin D deficiency or elevated inflammation markers.